OPTIMIZING THE ECOLOGICAL FUNCTIONS OF PUBLIC GREEN SPACE IN KLOJEN SUB-DISTRICT, MALANG CITY - Nurul Aini; Rima Dewi Supriharjo; Haryo Sulistyarso (Journal of Architecture&ENVIRONMENT, 2015)
Malang city has a high level of construction development causing many conversions of green open space into developed areas. One region that has a lot of green open space conversion into developed areas is Klojen Sub-Distric. The converted area is used to built a shopping center, residential areas and regional government office. This causes some environmental degradation, including increasing of air temperature in Malang city and reduced ability of green open space to produce oxygen. The purpose of this research is to optimize the ecological functions of green open space in Klojen Malang. The ecological functions that will be discussed are green open space as oxygen producer and as air temperature controller.The approach used in this research is positivistic, as the basis of experimental studies which use quantitative methods to verify the research hypothesis. The research type is a combination of descriptive and quantitative using techniques such as mapping analysis, characteristics of plant components and softscape analysis, oxygen demand analysis, biomass analysis, inter polation analysis, the average daily air temperature analysis, scoring analysis and descriptive analysis of green open space optimization.The results obtained in this research are to optimize the ecological function of green open space by adding 1216 trees, to increase frequency value and density. Criteria are suggested for the additional trees, to be suited to the characteristics of each open green space. Based on the optimization concept, the oxygen demand can be reduced by 42.3%. Moreover, it can also reduce the air temperature of public green open space to a minimun ideal urban air temperature, which is 27,5 oC.